Integrated system for training of aviation specialists - Stankunas, J. (Proceedings of National Aviation University (archive), 2001)
Co-operation between university and industrial potential is one of the most effective ways of organizing expensive studies in a small country. Co-operation between civil universities and military schools and structures is expedient in preparing reserve military specialist. An integrated system for the preparation of the specialists of civil and military aviation is precondition for the development of integrated management system of aviation and air space